PERANAN KENAIKAN HARGA GABAH DALAM PEREKONOMIAN INDONESIA TAHUN 2008 - Anda, Triyanto; Nuryadin, Didi (Jurnal Ekonomi & Studi Pembangunan, 2011)
Abstract: This study aims to determine the role of unhulled paddy price increases in Indonesia's economic output, employment, and also for the welfare of farmers in Indonesia. The research data in the form of secondary data obtained from the Statistics Indonesia as unhulled paddy prices in Indonesia, GDP growth by sector, rural inflation in Indonesia, Indonesian final demand, employment Indonesia, and the Indonesia Input-Output tables. This study uses analytical techniques influence the government benchmark price to the price of unhulled paddy and input output analysis techniques. The results showed that the industrial sector of food, beverages, and tobacco, and other industries, as well as transport and communications sectors are the potential sectors that have the index of distribution power and the index of sensitivity degree. During the period 1987-2007, farmer terms of trade in seven national rice producing provinces had developed quite fluctuate mainly between 1997-2008. In general, the level of relative prosperity, or the purchasing power of the farmers did not increase significantly.Â Â Abstrak: Studi ini bertujuan mengetahui peranan kenaikan harga gabah pada output perekonomian di Indonesia, kesempatan kerja, dan juga pada kesejahteraan petani di Indonesia. Data penelitian berupa data sekunder yang diperoleh dari Badan Pusat Statistik (BPS) seperti harga gabah di Indonesia, perkembangan Produk Domestik Bruto menurut sektor, perkembangan inflasi pedesaan di Indonesia, permintaan akhir Indonesia, ketenagakerjaanIndonesia, dan tabel Input-Output Indonesia. Penelitian ini menggunakan teknik analisis pengaruh harga patokan pemerintah terhadap harga gabah dan teknik analisis input ouput. Hasil penelitian menunjukkan bahwa sektor industri makanan, minuman, dan tembakau; industri lainya serta; serta sektor pengangkutan dan komunikasi merupakan sektor-sektor yang potensial karena memiliki indeks daya penyebaran dan indeks derajat kepekaan tinggi. Selama periode 1987-2007, Nilai Tukar Petani (NTP) di tujuh provinsi penghasil padi nasional mengalami perkembangan yang cukup berfluktuasi terutama antara 1997-2008. Secara umum tingkat kesejahteraan relatif, atau daya beli masyarakat petani tidak mengalami kenaikan yang signifikan.